Queue System Analysis in Improving Service Efficiency at Disdukcapil (Case Study at Bale Madukara Purwakarta) - Talitha Sahda Cahyadewi; Eka Ludiya (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
The high demand for population administration services at the Bale Madukara Population and Civil Registration Office in Purwakarta Regency has resulted in long queues and waiting times, especially during peak hours. This study aims to analyze the implementation of the queuing system and evaluate service performance in improving the efficiency of population administration services using the Multi Channel–Multi Phase model. The research method used was descriptive qualitative with data collection techniques through observation, interviews, and documentation. The research population was the social situation of population administration services, with a sample consisting of key informants, including the head of the service section, counter officers, and queue system managers. The results of the study show that the queuing system has implemented the multi-channel–multi-phase model, but in some service phases there is still a backlog of applicants due to the high arrival rate and limited service capacity. Therefore, it is necessary to adjust the number of counters, reorganize service flows, and continuously evaluate the queuing system in order to improve the efficiency and quality of public services.